2021
DOI: 10.3389/fsoc.2021.646854
|View full text |Cite
|
Sign up to set email alerts
|

Suicidal Ideations and Attempts Among Adolescents in Kampala Urban Settlements in Uganda: A Case Study of Adolescents Receiving Care From the Uganda Youth Development Link

Abstract: There is an increasing recognition that suicidal ideation is a major public health concern in sub-Saharan Africa. We employed a case study design, taking a case study of adolescents currently under the care of Uganda Youth Development Link (UYDEL). The data analyzed were collected from 219 female and male adolescents (13–19 years) recruited through UYDEL in Kampala, Uganda. A Poisson regression model with robust variance was used to assess the risk factors associated with suicidality. The prevalence of suicida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…Adolescents who categorized in severe and extremely severe anxiety scores, and those who reported chronic medical condition were at higher risk of experiencing suicidal ideation and suicidal. These results are in line with study findings of other African countries ( 12 , 32 , 39 , 40 ). Such consistent findings in different settings might be due to the fact that chronic pain and restlessness can lead adolescents to hopeless and prone to suicidal behaviors as a means of pain-relief.…”
Section: Discussionsupporting
confidence: 93%
“…Adolescents who categorized in severe and extremely severe anxiety scores, and those who reported chronic medical condition were at higher risk of experiencing suicidal ideation and suicidal. These results are in line with study findings of other African countries ( 12 , 32 , 39 , 40 ). Such consistent findings in different settings might be due to the fact that chronic pain and restlessness can lead adolescents to hopeless and prone to suicidal behaviors as a means of pain-relief.…”
Section: Discussionsupporting
confidence: 93%
“… 32 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 Among these studies, 43 were included in the meta-analytical process, for a total of around 65 million subjects (suicides: 63,120,235; suicidal behaviors: 934,951; suicidal ideation: 156,234): two reporting rates of deaths for suicides, 48 , 50 26 reporting prevalence data about suicidal behaviors 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 <...…”
Section: Resultsmentioning
confidence: 99%
“… Female: excess mortality was observed in March (5.3) and June (12.6) Charpignon ML, 2022 50 USA Observational 10–19 General population Annual number of suicides 2019: 41,852,838 2020: 41,715,352 2019: 2755 2020: 2806 Ehlman DC, 2022 49 USA Observational 10–14 General population Annual number of suicides 2019: 20,538,461 2020: 20,750,000 2019: 534 2020: 581 Isumi A, 2020 32 Japan Observational <19 General population IRR comparing the number of events from March to May in 2020 and in 2018–2019 NA NA The event rate significantly increased in May (IRR: 1.34, 95% CI 1.01–1.78) compared to March Matsumoto R, 2021 48 Japan Observational <19 General population Annual number of suicides (first 6 months of 2021) 2019: 21,691,777 2020: 21,404,883 2021: 21,037,601 2019: 21,691,777 2020: 21,404,883 2021: 404 Tanaka T, 2021 47 Japan Observational <19 General population Number of suicides February–June and July–October Feb–Jun 2019: Jul–Oct 2019: Feb–Jun 2020: Jul–Oct 2020: Feb–Jun 2019: Jul–Oct 2019: Feb–Jun 2020: Jul–Oct 2020: IRR first wave (February–June): 0.98, 95% CI: 0.75–1.27 IRR second wave (July–October): 1.49, 95% CI: 1.12–1.98 Panel B. Studies reporting prevalence data of suicidal behaviors Bukuluki P, 2021 51 Uganda Cross-sectional 13–19 General population Prevalence within the past 6 months (structured interview in August 2020) 219 53 The prevalence within the past 6 months preceding the survey was 24.2% (95% CI: 18.7–30.4) Carison A, 2021 52 …”
Section: Resultsmentioning
confidence: 99%
“…In Uganda studies on suicide among young people are based on community, clinical and school samples. The prevalence of suicidal ideation was 6.3% in a sample of university students ( 10 ); another study found that the prevalence of suicidal ideation among adolescents was as high as 30.6% ( 11 ). Among the refugees hosted in Uganda, the prevalence of suicidal ideation is 5% ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…Among the refugees hosted in Uganda, the prevalence of suicidal ideation is 5% ( 12 ). A range of factors are associated with suicidal ideation including financial difficulties ( 13 ), family breakdown or conflicts ( 14 ), and trauma ( 11 ), unemployment ( 10 ).…”
Section: Introductionmentioning
confidence: 99%